Mission profile oriented energy efficiency and CO2 footprint assessment of naval vessels at conceptual design phase: A comparative case study of conventional and hybrid energy systems - Cin, Selcuk; Celebi, Ugur Bugra (SAGE PUBLICATIONS LTD, 2025)
CO2 is the main green house gas (GHG) produced in fossil fuel burning engines on ships. The growth of activities of sea-going vessels, have been increasing interest and concerns over ship-born CO2 emissions. Consequently, numerous studies have been introduced for emission estimation. Each estimation approach has its own assumptions, thus uncertainty with data of vessel activities, vessel attributes, and calculating methods. The conceptual design phase is the first phase of ship design. One of the issues addressed at this phase is the assessment of energy system alternatives of relevant ship. A ship energy system provides propulsion and electrical power. The assessment of energy system alternatives for a naval vessel is a very complicated business that has a significant impact and interaction on overall vessel integration. Naval vessels and their energy systems constitute a noteworthy part of the total world ship fleet. The present study aims to present a realistic methodology for estimating efficiency, hence CO2 emissions, for candidate energy systems of surface vessels at conceptual design phase. A frigate is selected as the case (baseline) vessel. Three energy systems, namely CODAD, CODOG, and CODLOG-CC, are proposed as alternatives for the case vessel. Instead of general emission estimation approaches, the present study proposes a mission profile-oriented estimation methodology which provides more precise and accurate results. The Energy Efficiency Design Index (EEDI) defines efficiency and sets limitation during design and construction of specific merchant vessels, but since this index does not comply with unique characteristics of mission profile of surface vessels, the novel efficiency design index defined as integral warship EEDI (IWEEDI) is implemented for the case vessel. According to the analysis, CODAD is found to be the most efficient alternative, followed by CODLOG-CC and CODOG, respectively.
Keywords: Surface vessel; propulsion; energy; EEDI; efficiency; greenhouse gases; IWEEDI; CO2; GREENHOUSE-GAS EMISSIONS; REDUCING GHG EMISSIONS; OF-THE-ART; EXHAUST EMISSIONS; SHIPPING EMISSIONS; AIS DATA; SHIPS; POWER; CONSUMPTION; IMPACT; Engineering